Rational and Experiential Decision-Making Preferences of Third-Year Student Pharmacists - McLaughlin, Jacqueline E. (American Journal of Pharmaceutical Education, 2014)
Objective. To examine the rational (systematic and rule-based) and experiential (fast and intuitive) decision-making preferences of student pharmacists, and to compare these preferences to the preferences of other health professionals and student populations. Methods. The Rational-Experiential Inventory (REI-40), a validated psychometric tool, was administered electronically to 114 third-year (P3) student pharmacists. Student demographics and preadmission data were collected. The REI-40 results were compared with student demographics and admissions data to identify possible correlations between these factors. Results. Mean REI-40 rational scores were higher than experiential scores. Rational scores for younger students were significantly higher than students aged 30 years and older (p<0.05). No significant differences were found based on gender, race, or the presence of a prior degree. All correlations between REI-40 scores and incoming grade point average (GPA) and Pharmacy College Admission Test (PCAT) scores were weak. Conclusion. Student pharmacists favored rational decision making over experiential decision making, which was similar to results of studies done of other health professions.